Formaldehyde-Responsive Proteins TtmR and EfgA Reveal a Trade-off between Formaldehyde Resistance and Efficient Transition to Methylotrophy in Methylorubrum extorquens - Bazurto, Jannell V. (J Bacteriol, 2021)
For bacteria to thrive, they must be well adapted to their environmental niche, which may involve specialized metabolism, timely adaptation to shifting environments, and/or the ability to mitigate numerous stressors. These attributes are highly dependent on cellular machinery that can sense both the external and intracellular environment. Methylorubrum extorquens is an extensively studied facultative methylotroph, an organism that can use single-carbon compounds as its sole source of carbon and energy. In methylotrophic metabolism, carbon flows through formaldehyde as a central metabolite; thus, formaldehyde is both an obligate metabolite and a metabolic stressor. Via the one-carbon dissimilation pathway, free formaldehyde is rapidly incorporated by formaldehyde activating enzyme (Fae), which is constitutively expressed at high levels. In the presence of elevated formaldehyde levels, a recently identified formaldehyde-sensing protein, EfgA, induces growth arrest. Here, we describe TtmR, a formaldehyde-responsive transcription factor that, like EfgA, modulates formaldehyde resistance. TtmR is a member of the MarR family of transcription factors and impacts the expression of 75 genes distributed throughout the genome, of which many encode transcription factors and/or are involved in stress response, including efgA. Notably, when M. extorquens is adapting its metabolic network during the transition to methylotrophy, efgA and ttmR mutants experience an imbalance in formaldehyde production and a notable growth delay. Although methylotrophy necessitates that M. extorquens maintains a relatively high level of formaldehyde tolerance, this work reveals a trade-off between formaldehyde resistance and the efficient transition to methylotrophic growth and suggests that TtmR and EfgA play a pivotal role in maintaining this balance. IMPORTANCE All organisms produce formaldehyde as a by-product of enzymatic reactions and as a degradation product of metabolites. The ubiquity of formaldehyde in cellular biology suggests that all organisms have evolved mechanisms of mitigating formaldehyde toxicity. However, formaldehyde sensing is poorly described, and the prevention of formaldehyde-induced damage is understood primarily in the context of detoxification. Here, we used an organism that is regularly exposed to elevated intracellular formaldehyde concentrations through high-flux one-carbon utilization pathways to gain insight into the role of formaldehyde-responsive proteins that modulate formaldehyde resistance. Using a combination of genetic and transcriptomic analyses, we identified dozens of genes putatively involved in formaldehyde resistance, determined the relationship between two different formaldehyde response systems, and identified an inherent trade-off between formaldehyde resistance and optimal transition to methylotrophic metabolism.